2011
DOI: 10.1186/1478-4505-9-6
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction, feasibility and reliability of satisfaction questionnaire among patients with pulmonary tuberculosis in urban Uganda: a cross-sectional study

Abstract: BackgroundA comprehensive understanding of the barriers to and facilitators of poor tuberculosis (TB) treatment outcome is still lacking; posing a major obstacle to finding effective solutions. Assessment of patient satisfaction in TB programs would contribute to the understanding of gaps in healthcare delivery and the specific needs of individual patients. However, tools for assessing patient satisfaction are lacking.ObjectiveTo establish patient satisfaction, the feasibility and reliability of a questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 13 publications
2
30
0
1
Order By: Relevance
“…This community thought quality of health care was better in private facilities compared to government ones, which is also reported elsewhere, 34,35 and reduces utilisation of services as well. 36 Indeed, it is well known that the poor attitudes of health workers towards patients, including pregnant women, is a major contributory factor in shunning of facilities.…”
Section: Discussionsupporting
confidence: 76%
“…This community thought quality of health care was better in private facilities compared to government ones, which is also reported elsewhere, 34,35 and reduces utilisation of services as well. 36 Indeed, it is well known that the poor attitudes of health workers towards patients, including pregnant women, is a major contributory factor in shunning of facilities.…”
Section: Discussionsupporting
confidence: 76%
“…There have been several studies of tuberculosis patient satisfaction regarding treatment received, 1 , 7 , 10 with descriptive national findings consistent with the observed trend of elevated satisfaction. Although these national studies suggest explanations or factors influencing user satisfaction, they are restricted to specific contexts, not based on probability samples and lacking analytical approaches capable of differentiating between levels of satisfaction.…”
Section: Introductionmentioning
confidence: 53%
“… 1 It was observed that younger and more educated patients reported lower satisfaction levels, which may be related to higher standards of expectations, and, surprisingly, patients with high school reported higher satisfaction levels than those that had, at the most, reached the end of secondary education.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Wessels et al (2010) found that amongst oncology patients women rated care aspect of services more highly. A recent Ugandan study found some gender and age difference in patient satisfaction with TB services (Babikako et al 2011). Past experience and consequently patient expectations, they argue might influence age and gender differences in patient satisfaction.…”
Section: Discussionmentioning
confidence: 98%